Reversal of Multidrug Resistance by the Chinese Medicine Yiqi Jianpi Huaji Decoction and the Mechanism of Action in Human Gastric Cancer SGC7901/VCR Cells. (2nd February 2015) - Li, Wei-Bing; Li, Yang; Yu, Chen; He, Yong-Ming
Abstract : Yiqi Jianpi Huaji Decoction (YJHD), a traditional Chinese medicinal formula composed of twelve ingredients, has recently been reported to have a good clinical curative effect. The purpose of the present study was to evaluate the effects of YJHD on SGC7901/VCR gastric cancer cells and to elucidate the possible mechanism of action. First, the effects of a low dose of YJHD in combination with chemotherapeutic agents on SGC7901/VCR cells were assessed using the CCK-8 assay and flow cytometry, and the effects of YJHD on genes and proteins involved in drug resistance (MDR1, MRP, TUBB3, STMN1, and TS) were evaluated. Furthermore, transfection of SGC7901/VCR cells with siRNAs targeting these genes inhibited their expression, and the efficacy of vincristine against the cells was dramatically improved in vitro when these genes were silenced. These results demonstrate that low-dose YJHD inhibited cell proliferation, induced apoptosis, reversed MDR, and increased sensitivity to chemotherapeutic agents in vitro by downregulating P-gp, MRP, TUBB3, and STMN1 expression. MDR can be reversed by siRNAs targeting genes involved in MDR, and this strategy for cancer treatment should be evaluated in future studies.